Fiscalidad directa de la economía digital - Reyes Sarmiento, Javier Enrique (2021)
The globalization of the economy, the development of technology and the proliferation of digital services has generated the appearance of a new international tax order, this given the insufficiency of the traditional subjection criteria —source and residence— with the purpose of tax this source of wealth. It is in this context, with an accentuated need for resources from all nations, that today the world is discussing the need for a new nexus for the digital economy; however, the current proposals are developed around the possibility of developed countries to tax such a source, which despite being countries of residence of the companies that provide these digital services, today are also identified as countries of the source of this source of wealth. In the present work, the author analyzes the current context of the taxation of non-domiciled digital companies, addressing it from a historical point of view, and then observe its legal development at the international level.